Chrysin Induces Apoptosis and Autophagy in Human Melanoma Cells via the mTOR/S6K Pathway - Jae-Han Lee; Eun-Seon Yoo; So-Hee Han; Gi-Hwan Jung; Eun-Ji Han; Eun-Young Choi; Su-ji Jeon; Soo-Hyun Jung; BumSeok Kim; Sung-Dae Cho; Jeong-Seok Nam; Changsun Choi; et al. (Biomedicines, 2022)
Chrysin is known to exert anti-inflammatory, antioxidant, and anticancer effects. The aim of this study was to investigate the anticancer effects of chrysin in the human melanoma cells A375SM and A375P. The results obtained demonstrated successful inhibition of the viability of these cells by inducing apoptosis and autophagy. This was confirmed by the level of apoptosis-related proteins: Bax and cleaved poly (ADP-ribose) polymerase both increased, and Bcl-2 decreased. Moreover, levels of LC3 and Beclin 1, both autophagy-related proteins, increased in chrysin-treated cells. Autophagic vacuoles and acidic vesicular organelles were observed in both cell lines treated with chrysin. Both cell lines showed different tendencies during chrysin-induced autophagy inhibition, indicating that autophagy has different effects depending on the cell type. In A375SM, the early autophagy inhibitor 3-methyladenine (3-MA) was unaffected; however, cell viability decreased when treated with the late autophagy inhibitor hydroxychloroquine (HCQ). In contrast, HCQ was unaffected in A375P; however, cell viability increased when treated with 3-MA. Chrysin also decreased the phosphorylation of mTOR/S6K pathway proteins, indicating that this pathway is involved in chrysin-induced apoptosis and autophagy for A375SM and A375P. However, studies to elucidate the mechanisms of autophagy and the action of chrysin in vivo are still needed.